2021
DOI: 10.1021/acsanm.1c00224
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticles Decorated with Gadolinium Oxide Nanoparticles for Magnetic Resonance and Optical Imaging of Tumors

Abstract: structured nanoprobe that incorporates water-soluble silica and water-interacted gadolinium oxide, endowed with excellent hydrophilicity and high magnetic resonance imaging (MRI) relaxivity. The nanoprobes are monodispersed and uniformed with a superior stability due to the formation of Gd−O−Si bonds. The nanoprobe possesses an MRI relaxivity of 39.08 mM −1 s −1 , 9.3 times that of clinical Gd chelates, gaining a significant MRI enhancement in vivo; the classical Solomon− Bloembergen−Morgan theory is applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…12,13 Also doping the gadolinium oxide particles with mesoporous silica enhanced T1 contrast of gadolinium due to silica geometrical connement. [14][15][16] Recent studies have revealed that the conjugation of Gd 3+ complexes with iron oxide NPs, and the combination of Gd 2 O 3 NPs with other magnetic materials, such as Fe 3 O 4 NPs into single composite particles leads to the enhancement of T1 and T2 contrast in MRI. In case of a thin gadolinium shell, nanocomposites provided higher relativity than a thick shell during MRI examinations.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Also doping the gadolinium oxide particles with mesoporous silica enhanced T1 contrast of gadolinium due to silica geometrical connement. [14][15][16] Recent studies have revealed that the conjugation of Gd 3+ complexes with iron oxide NPs, and the combination of Gd 2 O 3 NPs with other magnetic materials, such as Fe 3 O 4 NPs into single composite particles leads to the enhancement of T1 and T2 contrast in MRI. In case of a thin gadolinium shell, nanocomposites provided higher relativity than a thick shell during MRI examinations.…”
Section: Introductionmentioning
confidence: 99%
“…3.0 g of carbamide, 1 mmol of Gd(NO 3 ) 3 •6H 2 O, Ln(NO 3 ) 3 •6H 2 O, and Yb(NO 3 ) 3 •5H 2 O with a relative molar ratio of 83:2:15 were dissolved into the as-prepared AuNSs colloidal solution and heated at 80 °C under water bath with forceful stirring for 5 h. After centrifugation at 8000 rpm for 8 min, the precursors were acquired and washed with deionized water and ethanol followed by drying in a vacuum refrigerant drier at minus 40 °C for 6 h. The AuNSA@Gd 2 O 3 :Yb 3+ /Ln 3+ (A-LnNPs) were successfully fabricated after being heated at 800 °C in a stove for 5 h and cooled down spontaneously (figure S1 (available online at stacks.iop.org/NANO/32/435201/mmedia)). The fabrication of SiO 2 nanocores, AuNSs and SiO 2 @Gd 2 O 3 :Yb 3+ /Ln 3+ NPs (S-LnNPs) [25] are supplied in supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…During recent decades, much attention has been devoted to the T1 MRI contrast agents, since the T2 mode of MRI can be confused with hypointense lesions and the blooming effect generated by SPIONs 3 . Different T1 contrast agents based on the Gd 3+ are gadolinium doped iron oxide 4 , gadolinium PGMA-based supramolecular polycations (PGEDGd@PGEAs) 5 , gadolinium oxide nanoparticles (Gd 2 O 3 ) 6 , and gadolinium functionalized carbon materials (graphene oxide 7 , carbon nanotube 8 , fullerene 9 ). However, most of the mentioned T1 contrast agents are single-modal only for MRI 3 .…”
Section: Introductionmentioning
confidence: 99%